Pelatihan Digital Marketing Untuk Meningkatkan Potensi Wisata Kampung Coklat Majapahit Di Kecamatan Dlanggu Kota Mojokerto: indonesia - tegowati stiesia; In’am Widiarma; Yayah Atmajawati (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
Cocoa is one of Mojokerto regency's mainstay commodities and has been developed in 2010 in 12 sub-districts and making the Dlanggu sub-district a development center. In developing cocoa, farmers need financing, increased knowledge related to cocoa plant pest prevention, product packaging and online marketing. So the Financial Services Authority (OJK) together the East Java Provincial Plantation Service & East Java BPR who are members of the East Java Province Regional Financial Access Acceleration Team (East Java TPAKD) held a